The Potential of Commercial Biomass-Based Activated Carbon to Remove Heavy Metals in Wastewater – A Review - Vina Rofikoh; Badrus Zaman; Budi Prasetyo Samadikun (School of Postgraduate Studies, Diponegoro Univer, 2024)
Commercial activated carbon is a type of adsorbent commonly used in adsorption processes. However, the use of commercial carbon in wastewater treatment is still limited, due to the scarce availability of precursors and their high cost. Biomass as an activated carbon precursor has been reported to have high efficiency in removing various heavy metals in wastewater. This study aims to review the potential of biomass-based activated carbon to adsorb heavy metals in terms of biomass constituent components, heavy metal removal, and future prospects. The method in this study is a systematic literature review, or SLR, to collect data from online databases such as Google Scholar, PubMed, and ScienceDirect. The results show that biomass-based activated carbon is effective in the removal of heavy metals in various types of wastewater. The removal effectiveness for different types of biomass ranged from 84–99% for Pb2+ ions, 55–92% for Cd2+ ions, 84–99% for Pb2+ ions, 96% for As2+ ions, 80–100% for Cr2+ ions, 25–97% for Fe2+ ions, 50–99% for Ni2+ ions, and 62–98% for Cu2+ ions, and 98% for Ti ions. These results show that heavy metals have different affinities to activated carbon from biomass, from all heavy metals, Fe2+ and Cd2+ ions have the lowest affinity, so the activated carbon used to remove Fe2+ and Cd2+ metals needs to be produced with higher porosity and surface area. The removal of heavy metals using activated carbon from biomass is limited by adsorbent dosage, contact time, solution pH, temperature, initial adsorbate concentration, particle size, and stirring speed. In future research, it is expected that activated carbon from biomass has a high adsorption capacity, is economical cost, is environmentally friendly and can be used on a larger scale.